The Effect of Kinesiotaping on Hand Function in Patients with Rheumatoid Arthritis (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2016)
Research background. Physical therapy is one of the main methods of rehabilitation in order to maintain and improve hand function for patients with rheumatoid arthritis. It is supposed that kinesiotaping method can be successfully used in patients with RA during the physical therapy to improve hand function. The aim of the research was to evaluate the effect of kinesiotaping on hand function in patients with Rheumatoid Arthritis. Methods. The study involved 22 subjects (100% women) who had Rheumatoid Arthritis. Subjects were randomly divided into two groups: the research group consisted of 10 individuals, they received kinesiotaping and exercise program, and the control group consisted of 12 individuals, only exercise was applied to them. The study lasted for 2 months, the procedures were performed three times a week. Range of motion of the wrist was measured using the goniometry method, the handgrip strength was assessed using a dynamometer. Modifed Keitel Function test and Modifed Arthritis Impact Measurement Scale (AIMS II) were used to evaluate hand function. Results. Range of motion of the wrist after physical therapy increased in both groups, but in the research group the right and the left wrist ﬂexion and the left wrist extension were signifcantly higher than in the control group (p < 0.05). The hand grip strength after physical therapy signifcantly increased in the control and in the research groups (p < 0.05), but in the research group, it was significantly higher than in the control group (p < 0.05 ). Hand functional status assessed by using a modifed Keitel index improved in both groups (p < 0.05) was significantly better in the research group (p < 0.05). The hand function assessed by the Arthritis Impact Measure Scale signifcantly improved in both groups (p < 0.05), but no signifcant difference between the groups was observed (p > 0.05). Conclusion. Kinesiotaping in conjunction with physical therapy is more effective method than just physical therapy in order to increase the range of motion of the wrist, the hand grip strength and hand functional status of patients with RA.Keywords: rheumatoid arthritis, physical therapy, kinesiotaping.